The main aspects of sports training are tactical, technical, mental training - Prof. J.E.Eshnazarov; Kholdorov Zokhid Abduvayitovich (Genius Journals, 2022)
This article plays an important role in improving the tactical, technical and mental training of athletes, which are key aspects of their training, and getting acquainted with their effective methods.
Keywords: tactical movement; tactical action phases movement acceptor; tactical training method; free maneuver